Characterisation of the Gillenia S-locus provides insight into evolution of the nonself-recognition self-incompatibility system in apple - Ruiling Wang; Cecilia H. Deng; Amandine Cornille; William Marande; Elena López-Girona; Toshi Foster; Deepa Bowatte; Ting-Hsuan Chen; David Chagné; Robert J. Schaffer; Hilary S. Ireland (Scientific Reports)
Abstract Self-incompatibility (SI) in plants has evolved independently multiple times and S-RNase-based gametophytic self-incompatibility (GSI) is most common. The Rosaceae family possesses both self-recognition (Prunus) and nonself-recognition (Malus) GSI systems, and the latter is widespread in flowering plants. Gillenia trifoliata is a Rosaceae species related to Prunus and Malus, providing utility for understanding SI evolution. Gillenia is sister taxon to Malus, but unlike Malus, has not undergone polyploidisation. In addition, the common ancestor of Gillenia and Prunus is close to the origin of the subfamily. Using a highly contiguous Gillenia genome, orthologous regions to both Malus and Prunus S-loci were identified. Only the Prunus-like S-locus was highly polymorphic and had signatures of a functional S-locus including positive selection of the S-RNase. This suggests a self-recognition system controls SI in Gillenia, and the common ancestors of Gillenia and Prunus, and Gillenia and the apple tribe, likely had a self-recognition SI system. Comparative genomics between Gillenia and Malus suggest apple lost the self-recognition mechanism, and a nonself-recognition mechanism evolved independently from a rudimentary locus with at least one male S-determinant. Repetitive sequences in the Malus-like S-locus in Gillenia may facilitate illegitimate recombination, suggesting putative mechanisms of evolution of nonself-recognition S-loci.